As licitações públicas como um mecanismo para a promoção do desenvolvimento sustentável: um estudo na Universidade Tecnológica Federal do Paraná - Beltrame, Franciele Malaguti (2017)
The objective of this research was to analyze the perceptions of the bidding process managers, Campi of Dois Vizinhos, Francisco Beltrão and Pato Branco of the University Techonological Federal of Paraná on bidding and their contribution to the promotion of sustainable development. For the data analysis, it was based on the methodological support of the content analysis and among the set of techniques systematized by the referred method, it was used of the analysis by categories. Data were collected through a free evocation questionnaire, consisting of a free evocation question and two writing questions and semi-structured interviews, both of which were homogeneously applied to the three respondent segments, which included pregoers, planning and administration directors and general directors of the research locus. It was concluded that, in general, the process of implementation of sustainable bids is still incipient in the research locus, which leads to considerable evolution, both by the Institution and the supplier market, in order to guarantee competitiveness, an essential factor to the bidding process. In addition, it is perceived that the change of this scenario will occur gradually and in the long term, demanding that some barriers be transposed, especially the informational barrier, that can be overcome through the continuous training, since what is verified is that there is no resistance in the implementation, there is a lack of knowledge and familiarity regarding the whole theme that involves sustainable biddings. It was also verified that the legislation was the aspect considered most important by the managers to translate the bid, followed by the economical, the transparency and the planning. In this way, the importance attributed to conventional aspects and the absence of any inference referring to the promotion of sustainable development or the insertion of socio-environmental criteria is evident, although this purpose is expressly stated in Article 3 of the General Law on Tenders. Therefore, it is concluded that referred insertion, promoted by Law no. 12,349 / 2012, which made the promotion of sustainable development an obligation for all public managers was not enough for the effective insertion of socio-environmental criteria in the bidding documents.